A review of the metastable omega phase in beta titanium alloys: the phase transformation mechanisms and its effect on mechanical properties. (2nd January 2023) - Ballor, JoAnn; Li, Tong; Prima, Frédéric; Boehlert, Carl J.; Devaraj, Arun
ABSTRACT: Since its discovery in 1954, the omega (ω) phase in titanium and its alloys has attracted substantial attention from researchers. The β-to-ω and ω-to-α phase transformations are central to β-titanium alloy design, but the transformation mechanisms have been a subject of debate. With new generations of aberration-corrected transmission electron microscopy and atom probe tomography, both the spatial resolution and compositional sensitivity of phase transformation analysis have been rapidly improving. This review provides a detailed assessment of the new understanding gained and related debates in this field enabled by advanced characterization methods. Specifically, new insights into the possibility of a coupled diffusional-displacive component in the β-to-ω transformation and key nucleation driving forces for the ω-assisted α phase formation are discussed. Additionally, the influence of ω phase on the mechanical properties of β-titanium alloys is also reviewed. Finally, a perspective on open questions and future direction for research is discussed.